Making it work : educating the blind/visually impaired student in the regular school - Castellano, Carol, 1951- (Critical concerns in blindness., 2005)
Making It Work is destined to be the definitive guide for years to come on how to make the regular school education a successful experience for blindvisually impaired children. With chapters flowing logically and full of detailed, useful information, it will be an essential handbook for school staff, specialized service providers, and parents of blindvisually impaired children. This is an exquisite, enlightened guide for the education of blindvisually impaired children in the new millennium.